Sistem Kendali Lampu Taman serta Pengecekan Suhu dan Kelembapan di Sekitar Menggunakan NodeMCU ESP8266 Berbasis Internet Of Things - Sultan Raza Fiqri; Abdul Jabbar Lubis; Risko Liza (SEMINAR NASIONAL TEKNOLOGI INFORMASI & KOMUNIKASI, 2021)
Advances in technology today have provided many benefits in the use of electronic equipment that makes it easier for humans to carry out their daily activities. In the Industrial revolution 4.0, the first progress that can be felt is the internet of things or IoT. Iot has an important role in Industry 4.0, because it can connect everything to the internet network. Iot (Internet of Things) can be used in gardens to control garden lights and check temperature and humidity that can be operated remotely via the internet. This system utilizes sensors that can detect the amount of light intensity resistance that is used to turn on and off lights based on light intensity, sensors that can detect temperature and humidity that can be controlled and monitored from anywhere and anytime. In this study, the system uses a nodemcu esp8266 microcontroller which functions as a device that activates all components, such as the dht11 sensor, ldr sensor, 2 channel relay and led lights. This system uses a telegram application that functions as an application for controlling lights and checking temperature and humidity which is accessed from a smartphone connected to the nodemcu esp8266 microcontroller via a wifi network. The results of the trials carried out on all the features showed the results as expected.